2020
DOI: 10.1111/dth.14334
|View full text |Cite
|
Sign up to set email alerts
|

Measuring perceived benefit and disease‐related burden in patients affected with vulvar lichen sclerosus after a standard topical corticosteroid treatment. Results from a cohort study using Pictorial Representation of Illness and Self‐measure and Dermatology Life Quality Index

Abstract: Improvement in suffering after treatment has been poorly investigated in women affected with vulvar lichen sclerosus (VLS). We performed an observational study on a cohort of VLS patients for assessing the effect of a 12-week topical corticosteroid treatment on their VLS-related burden, as measured with Pictorial Representation of Illness and Self-Measure (PRISM) and Dermatology Life Quality Index (DLQI). Demographics and disease-related subjective and objective scores (at baseline, T0, and at the control visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
3
9
0
Order By: Relevance
“…Additionally, while based on these data we cannot grade patients in terms of clinical response, other studies have demonstrated improvement in DLQI and PRISM scores from baseline as compared to after a 12-week treatment course of topical corticosteroids. 18 …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, while based on these data we cannot grade patients in terms of clinical response, other studies have demonstrated improvement in DLQI and PRISM scores from baseline as compared to after a 12-week treatment course of topical corticosteroids. 18 …”
Section: Resultsmentioning
confidence: 99%
“…This seems to indicate that all these diseases cause greater suffering than MM, an apparently paradoxical datum that could have several possible explanations. In our experience, albeit limited to subjects affected with inflammatory genital disorders, disease-related symptoms are the main determinants of the PRISM score [ 17 , 18 ]. As previously excised, MM does not usually cause symptoms, unlike many of the other non-neoplastic diseases listed above; this could at least partially justify the difference in mean PRISM scores between conditions characterized by chronic, distressing symptoms and others without.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, unlike in trials, there is the need for rapid tools, easily understood by subjects of any cultural and social level. Our group has recently tested the use of Pictorial Representation of Illness and Self Measure (PRISM) for assessing the burden of suffering from inflammatory skin disorders, in particular of the genital area [ 17 , 18 ]. It is a visual, non-verbal instrument aimed at quantitatively assessing the burden of illness-related suffering [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may be bypassed by using nonverbal instruments, such as Pictorial Representation of Illness and Self Measure (PRISM). This represents a valid tool in defining the impact of issues whose verbalization can determine feelings of shame and embarrassment and has been validated in both dermatological [15][16][17][18][19][20][21][22][23] and non-dermatological disorders [24][25][26][27][28] even concerning the effectiveness of therapy [29,30].…”
Section: Introductionmentioning
confidence: 99%